2008
DOI: 10.1038/emboj.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian target of rapamycin complex 2 controls folding and stability of Akt and protein kinase C

Abstract: The target of rapamycin (TOR), as part of the rapamycinsensitive TOR complex 1 (TORC1), regulates various aspects of protein synthesis. Whether TOR functions in this process as part of TORC2 remains to be elucidated. Here, we demonstrate that mTOR, SIN1 and rictor, components of mammalian (m)TORC2, are required for phosphorylation of Akt and conventional protein kinase C (PKC) at the turn motif (TM) site. This TORC2 function is growth factor independent and conserved from yeast to mammals. TM site phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
510
5
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(552 citation statements)
references
References 43 publications
24
510
5
7
Order By: Relevance
“…F The TM of PKCf is dephosphorylated in cells treated with mTOR kinase inhibitors. 293T cells were treated with Torin1 (100 nM, lanes 1-4) or PP242 (1 lM, lanes [5][6][7][8] for the indicated time.…”
Section: Resultsmentioning
confidence: 99%
“…F The TM of PKCf is dephosphorylated in cells treated with mTOR kinase inhibitors. 293T cells were treated with Torin1 (100 nM, lanes 1-4) or PP242 (1 lM, lanes [5][6][7][8] for the indicated time.…”
Section: Resultsmentioning
confidence: 99%
“…More recent evidence has demonstrated that the mammalian Target of Rapamycin (mTOR) pathway regulates TM phosphorylation of some, but not all, PKCs [59][60][61]. mTOR is a serine/threonine kinase that associates with other proteins to form multi-protein complexes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…One of these complexes, mTORC1, is sensitive to the drug rapamycin while the other complex, mTORC2, is insensitive to acute rapamycin treatment [62]. mTORC2 has been implicated in TM phosphorylation of cPKCs ( , I , II , ) and PKC in murine embryonic fibroblasts (MEFs) [59,60]. In MEFs that lack critical components of the mTORC2 complex, the levels of expression of cPKCs and PKC are vastly reduced and TM phosphorylation is also absent on the residual pool of PKC (A-loop and HM phosphorylation are also absent).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations